From Natural Killer Cell Receptor Discovery to Characterization of Natural Killer Cell Defects in Primary Immunodeficiencies - Tabellini, Giovanna; Patrizi, Ornella; Dobbs, Kerry; Lougaris, Vassilios; Baronio, Manuela; Coltrini, Daniela; Plebani, Alessandro; Badolato, Raffaele; Notarangelo, Luigi D.; Parolini, Silvia (Frontiers in Immunology, 2019)
Alessandro Moretta was Professor of Histology at University of Brescia from 1994 to 1997. It was in that period that we met and started a collaboration that continued in the years to follow. He immediately involved us in the production of monoclonal antibodies (mAbs) that allowed the identification and fine characterization of novel receptor molecules that were able to activate or inhibit human Natural Killer cell function, including several antibodies specific for Natural Cytotoxicity Receptor (NCR) and Killer-cell Immunoglobulin-like Receptor (KIR) molecules. These reagents generated in our laboratory in Brescia contributed to complete the studies aimed to characterize innate lymphoid NK cells, that had been initiated by Alessandro and his brother Lorenzo in Genoa. Furthermore, under Alessandro’s guidance, we identified an anti-KIR3DL2 that was subsequently shown to be helpful for the diagnosis and treatment of various forms of cutaneous T cell lymphoma. While in Brescia, Alessandro established a partnership with those of us who were working in the Department of Pediatrics; together, we tackled the goal of studying the role of NK cells in patients with primary immunodeficiencies. This exciting collaboration led to novel discoveries that shed light on the critical role played by NK cells in the immune response against virus and tumors in humans, as best exemplified by our characterization of the molecular mechanisms of impaired control of Epstein-Barr Virus (EBV) infection in patients with X-linked lymphoproliferative (XLP) disease. After Alessandro left Brescia to return to Genoa, our collaboration continued with the same enthusiasm, and even from a distance he remained an extraordinary example of an inspirational and generous mentor. This review is a sign of our gratitude to a mentor and a friend whom we deeply miss.